The study of business development rubber plant people in the village Long Hubung districts Long Hubung district Mahakam Ulu - Floryanus Kerung; Zuhdi Yahya; Zikri Azham (Universitas 17 Agustus 1945 Samarinda, 2018)
The purpose of this study was to determine the types of trees at the potential and deployment Macaranga Spp haul roads around wood PT. Ratah Timber particularly at Km 23.26 and 30 villages Mamahak Teboq District of Long Hubung Mahakam Ulu Regency. Data collection and research done by the preparation method of sampling is done using a 20x20 meter plots were arranged in lines of research. Number of PU in daloam each path varies according to the field conditions, distance of between 9-10 plots.Also in the interview did also used to obtain data and information from officers in the field, officials of relevant agencies and the local population that has to do with the activities of research and from the literature that support.Research results can be sorted by diameter class is 10-15, 16-20, 21-30, and> 30 cm and are obtained 1) Volume Macaranga Spp tree on plot 1, 2 and 3 with a diameter of 10-15 cm class is 10 , 58 m³ with 236 trees, the diameter class 16-20 cm was 6.35 m³ there are 62 trees, while the volume with a diameter of 21-30 cm class is 15.64 m³ there are 75 trees while the number of overall diameter is 32.97 m³. Distribution Macaranga Spp tree most commonly found on the second plot with 173 trees including the number of trees under 10 cm in diameter (not measured).Suggestions submitted on the results of this study are 1) To the PT. Ratah Timber trying keep the existence and preservation of trees Macaranga Spp. existing in PT. Ratah Timber from forest fires disorders; 2) Keep an inventory of trees Macaranga Spp. on the whole area of PT. Ratah Timber to determine the distribution and potential Macaranga Spp.